Examining homogeneity of dielectric barrier discharge using dispersion normalization and local temperature difference methods - Yang, H.; Chen, M. M.; Zhang, H. T.; Zhou, F. S.; Zhang, L.; Sun, F.; Wang, X. (Frontiers in Physics, 2023)
The homogeneous discharge mode in dielectric barrier discharge (DBD) has sparked wide interest in recent years. Assessing the dielectric barrier discharge homogeneity value (DHV) offers value in the industry. The current method of assessing DHV involves distinguishing between the filamentous and homogeneous modes of discharge but struggles to qualitatively analyze it. This study proposes a method for evaluating DHV that involves using the dispersion normalization and the local temperature difference methods. The values of such parameters as the voltage, frequency, air gap, and gas flow were tested to verify the validity and generality of the proposed method. The results of experiments revealed that the dispersion normalization method uses information on the luminosity of the discharge image to assess the homogeneity of DBD under different conditions. The temperature difference in the area of discharge was also calculated to assess the homogeneity of DBD, and the results showed that it is useful to this end. Moreover, the dispersion coefficient and the difference in local temperature were found to be inversely proportional to DHV. The proposed method can thus be used to identify variations in DHV under different conditions, and provides a basis for its characterization.